Mechanisms of phosphene generation in ocular proton therapy as related to space radiation exposure. (August 2016) - Chuard, D.; Anthonipillai, V.; Dendale, R.; Nauraye, C.; Khan, E.; Mabit, C.; De Marzi, L.; Narici, L.
Abstract: Particle therapy provides an opportunity to study the human response to space radiation in ground-based facilities. On this basis, a study of light flashes analogous to astronauts' phosphenes reported by patients undergoing ocular proton therapy has been undertaken. The influence of treatment parameters on phosphene generation was investigated for 430 patients treated for a choroidal melanoma at the proton therapy centre of the Institut Curie (ICPO) in Orsay, France, between 2008 and 2011. 60% of them report light flashes, which are predominantly (74%) blue. An analysis of variables describing the patient's physiology, properties of the tumour and dose distribution shows that two groups of tumour and beam variables are correlated with phosphene occurrence. Physiology is found to have no influence on flash triggering. Detailed correlation study eventually suggests a possible twofold mechanism of phosphene generation based on ( i ) indirect Cerenkov light in the bulk of the eye due to nuclear interactions and radioactive decay and ( ii ) direct excitation of the nerve fibres in the back of the eye and/or radical excess near the retina.